Association between neutrophil-platelet ratio and 28-day mortality in patients with sepsis: a retrospective analysis based on MIMIC-IV database - Jin Zhu; Chaorong Zhang; Zhexuan Deng; Lifen Ouyang (BMC Infectious Diseases)
Abstract Background The immune system and inflammation are intimately linked to the pathophysiology of sepsis. The neutrophil‒platelet ratio (NPR), associated with inflammation and immunology, may be useful in predicting sepsis outcomes. According to earlier research, the NPR is linked to the prognosis of several diseases. This study aimed to investigate the connection between the NPR and unfavorable outcomes in patients with sepsis. Methods We retrieved patient clinical data from the Medical Information Mart for Intensive Care IV database (MIMIC-IV 2.2) based on the inclusion and exclusion criteria. The NPR quartile was used to divide the population into four groups. 28-day mortality was the main result, whereas 90-day mortality was the secondary result. The Cox regression model, Kaplan‒Meier survival curve, and limited cubic spline were used to examine the associations between the NPR and the negative outcomes of sepsis. Subgroup analysis was also conducted. At the same time, we used Latent Class Trajectory Model (LCTM) to assess the trajectory of NPR within six days of ICU admission, and to assess the relationship between NPR trajectory and mortality at 28 and 90 days. Results This study included 3339 patients. Quartile 4 had the greatest 28-day and 90-day mortality rates, according to the Cox regression model and Kaplan‒Meier survival curve. A J-shaped relationship between the NPR and mortality was found in restricted cubic spline investigations. This means higher and lower NPRs were linked to higher mortality, with NPR = 3.81 as the tipping point. A total of 434 patients were included in the trajectory analysis, and three trajectory patterns were identified. Patients with sepsis had an increased mortality rate in the slow-decline group compared with the stable development group. Conclusion The NPR has prognostic value for patients with sepsis, and there is a J-shaped relationship between the two variables. Patients with sepsis who have a slowly declining NPR have an increased mortality rate. Clinical trial Not applicable.